Utilization of Learning Media Using Used Cans in Sound Wave Material in Elementary Schools - Widyastika, Dinda (Cattleya Darmaya Fortuna, 2022)
Science is a subject that is very closely related to human life, science learning must be able to utilize existing resources in the surrounding environment so that it makes students easy to understand the lessons delivered because it is closely related to everyday life. The use of bekar tools can be used in science lessons such as milk cans can be used as a learning media tool to find out the sound waves produced by ropes and can be placed in the ear as a communication tool in ancient times. The wave being propagated requires an intermediate medium. Sound waves, for example, cannot be heard without an intermediary medium. Likewise, without a rope, it is impossible for a wave to propagate. In a rope with a greater tension, waves will propagate at a higher speed of propagation. Canned telephones using ropes are more clearly audible than wires,